Analysis of Undergraduate Training Given to Students with Hearing Impairment in their Acquisition of Professional Competences - Mariona DALMAU MONTALÀ; Ingrid SALA BARS (Siglo Cero, 2015)
The aim of this study was to understand how university graduates with a hearing impairment in Spain perceived their studies. The method used was quantitativequalitative and descriptive. The participating sample consisted of 84 Spanish university graduates with a hearing impairment. The results allow us to confirm that: university graduates with a hearing impairment, in general, are not provided with appropriate/ sufficient support at university to develop their professional competence; these graduates believe that employers consider good command of professional competences to be pivotal; professionalizing practices during university studies are an opportunity for the employment of graduates with hear impairment; finally, it is highlighted that university lecturers lack knowledge of the needs and difficulties of students with hearing impairment.